Amniotic membrane as a biological dressing in infected wound healing in rabbits - Duarte,Ian Göedert Leite (2014)
PURPOSE:To investigate amniotic membrane as a biological dressing in infected wound healing in rabbits.METHODS: The use of preserved amniotic membranes (AMs) was examined using 15 rabbits with experimentally induced wound infections on their backs. Healing was histologically evaluated during different phases including inflammation, granulation, epithelialization, and fibroplasia. The animals were distributed into three groups for histological study at seven, 14, 21, and 28 days post-wound induction. Group A did not receive treatment: the wound was left exposed and dry; Group B received a daily exposure treatment with collagenase; and Group C received one AM, which also remained exposed.RESULTS: A marked reduction of the inflammatory phase was observed in Group C at 21 days, and the granulation phase of this healing increased at 14 days. Epithelialization was similar among the three groups, and fibroplasia was more pronounced in Group C at 14 days. Furthermore, gradual collagen organization also began for the animals in Group B at 14 days.CONCLUSION:The amniotic membrane did not significantly alter the inflammation, epithelialization, or fibroplasia phases but did increase angiogenesis up to Day 14 compared with the dry dressing and collagenase treatments.